Analisis Manajemen Pemenuhan Kebutuhan Dokter Pada Rumah Sakit Umum Daerah Kabupaten Nunukan Kalimantan Utara - Utami, Nurul Riskya; Arif, Muhammad Ridwan; Rukaiyah, St (STIM-LPI Makassar, 2025)
This study aims to analyze the management of doctor fulfillment at the Regional General Hospital (RSUD) of Nunukan Regency, North Kalimantan. This research employs a qualitative approach with a descriptive method, prioritizing the collection of primary and secondary data through interviews, field observations, and document analysis. The findings indicate that while the management of doctor fulfillment at RSUD Nunukan has covered various essential aspects, improvements are still needed in the recruitment system, enhancement of workplace facilities, and the welfare of medical personnel. The main obstacles identified include the lack of incentives, limited medical facilities, as well as geographical challenges and complex bureaucratic procedures. This study provides recommendations to improve the recruitment system, increase incentives for medical personnel, and optimize budget management to better meet the demand for doctors and enhance the quality of healthcare services in the region.